2017
DOI: 10.1088/1361-6439/aa97b7
|View full text |Cite
|
Sign up to set email alerts
|

Burst pressure of phaseguide structures of different heights in all-polymer microfluidic channels

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In our previous study, 31 we demonstrated sequential sample dispensing into five microchambers (volume = 3 µL) by controlling the burst pressures in three types of phaseguide ridge structures (hereinafter referred to as lateral-type phaseguides 33,34 ) with different inclined angles against the flow direction, as presented in Fig. S1.…”
Section: Vertical-type Phaseguide Structure As a Passive Valvementioning
confidence: 99%
“…In our previous study, 31 we demonstrated sequential sample dispensing into five microchambers (volume = 3 µL) by controlling the burst pressures in three types of phaseguide ridge structures (hereinafter referred to as lateral-type phaseguides 33,34 ) with different inclined angles against the flow direction, as presented in Fig. S1.…”
Section: Vertical-type Phaseguide Structure As a Passive Valvementioning
confidence: 99%
“…The tumor section was surrounded by two microfluidic channels (1 mm width × 800 μm height) for the delivery of oxygen, nutrients, and therapeutic drugs and/or immune cells (Figure D,G). Cancer cells were loaded through cell injection ports to create 2-D and 3-D tumor sections by a liquid-pinning process, where a drop of cells with a desired number (in medium, for 2-D) or density (in ECM gel before curing) was injected and held underneath the central pillar by the surface tension at the liquid–air interface (Figure E,F). The device geometry and liquid pinning created a micropattern of cancer cell layer/bulk with the desired shape, area, and/or volume as a tumor model.…”
Section: Resultsmentioning
confidence: 99%
“…Liquid pinning was chosen to create a cancer cell monolayer or 3-D tumor section in our tumor model, for its ease of operation without requiring additional structural components (such as pillars) that may interfere with oxygen diffusion. It utilized surface tension at the liquid–substrate–air interface to hold the liquid within the small crevices of the device (i.e., the diffusion gap in the current design) (Figure D).…”
Section: Resultsmentioning
confidence: 99%
“…1d, where the NDG configuration is represented. CBVs are strictions within microfluidic channels providing a pinning interface for a forward proceeding fluid [19][20][21] . Classically, CBVs were designed to stop an advancing front from going further on, left or right 21,22 .…”
Section: A Device For Mechanical Compression Of Bi-layered 3d Microti...mentioning
confidence: 99%